In Daddy's arms I am tall : African Americans celebrating fathers - Steptoe, Javaka, 1971- (New York : Lee & Low Books, 1997)
A collection of poems celebrating African-American fathers by Angela Johnson, E. Ethelbert Miller, Carole Boston Weatherford, and others.
Wilson's Children, June 2001
Elem. School Library Collection, June 2000
Notable/Best Books (A.L.A.), January 1998
School Library Journal, February 1998
Book Links (A.L.A.), December 2002
Booklist starred, February 1998
Keywords: Children's poetry, American -- African American authors; Fathers -- United States -- Juvenile poetry; African American fathers -- Juvenile poetry; Men -- United States -- Juvenile poetry; African American men -- Juvenile poetry; Fathers -- Poetry; African Americans -- Poetry; American poetry -- Collections; Fathers -- Poetry; African Americans -- Poetry; African American men -- Poetry; American poetry -- African American authors